2000
DOI: 10.1097/00007691-200008000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Sirolimus (Rapamycin) in Whole Blood

Abstract: The effects of storage time (0-8 days), temperature (4 degrees C and 30 degrees C in dark and light), and freeze-thaw cycles on the stability of sirolimus in blood were examined. Sirolimus quantification was undertaken using HPLC-electrospray-tandem mass spectrometry. Whole blood samples supplemented with sirolimus (5.0, 15.0, and 30.0 microg/L) and pooled renal and heart transplant samples were found to be stable during the 8 days under all conditions (<10% decrease in concentration). No significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Blood samples were frozen at −80°C for 1 month prior to analysis, which might have adversely affected measurement of the rapamycin concentration in those samples. Results of other studies 24,25 indicate that the rapamycin concentration is not substantially affected in blood samples stored frozen at −80°C for 90 days and subsequently thawed. Therefore, we do not believe that blood sample storage prior to analysis significantly affected measurement of blood rapamycin concentration in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Blood samples were frozen at −80°C for 1 month prior to analysis, which might have adversely affected measurement of the rapamycin concentration in those samples. Results of other studies 24,25 indicate that the rapamycin concentration is not substantially affected in blood samples stored frozen at −80°C for 90 days and subsequently thawed. Therefore, we do not believe that blood sample storage prior to analysis significantly affected measurement of blood rapamycin concentration in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding long term stability, the present study highlights the possibility of storing samples up to 90 days at -20°C without significant variations, since an increment in drug concentrations <7% was found. In previous studies, Salm reported a substantial constancy of Siro concentrations in samples stored at -80°C for 6 weeks after one, two or three freezethaw cycles (9), while Streit reported a significant decrease after storing samples at -40°C for 6 months and after two freeze-thaw cycles (11). It is worth of note that in both previous trials the Authors used storage temperatures much lower than those presently worked.…”
Section: Discussionmentioning
confidence: 95%
“…In Table I 9 ) containing sirolimus (panels a-c) and everolimus (panels d-f In Fig. 3 LT o ' r = 0.786.…”
Section: Long Term Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…When using LC-MS/MS, it has been shown that blood samples retain their analytical integrity for up to 3 days at 30°C when kept in the dark [30]. At 35°C, there was a 9 % loss of the drug after 3 days of storage and a 13 % loss after 6 days [29].…”
Section: Hplc With Mass Spectrometric (Ms) Detectionmentioning
confidence: 99%